2015
DOI: 10.1371/journal.pone.0134882
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antileukemia Effect and Structural Analyses of SRPK Inhibition by N-(2-(Piperidin-1-yl)-5-(Trifluoromethyl)Phenyl)Isonicotinamide (SRPIN340)

Abstract: Dysregulation of pre-mRNA splicing machinery activity has been related to the biogenesis of several diseases. The serine/arginine-rich protein kinase family (SRPKs) plays a critical role in regulating pre-mRNA splicing events through the extensive phosphorylation of splicing factors from the family of serine/arginine-rich proteins (SR proteins). Previous investigations have described the overexpression of SRPK1 and SRPK2 in leukemia and other cancer types, suggesting that they would be useful targets for devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 53 publications
2
33
0
2
Order By: Relevance
“…Three chemical scaffolds have been described with inhibitory activities against SRPK1 (Batson et al, 2017; Morooka et al, 2015; Fukuhara et al, 2006; Siqueira et al, 2015; Székelyhidi et al, 2005; Gammons et al, 2013), and, among them, SPHINX31 was recently derived from SPHINX and reported to have much improved potency (Batson et al, 2017). Although high-throughput screening has been commonly used to generate lead compounds in kinase inhibitor projects, we chose to query existing kinase inhibitor libraries and known FDA-approved drugs for their potential abilities to target SRPK1, an approach that offers advantages in expediting structure-activity relationship (SAR) studies and optimizing pharmacological properties.…”
Section: Resultsmentioning
confidence: 99%
“…Three chemical scaffolds have been described with inhibitory activities against SRPK1 (Batson et al, 2017; Morooka et al, 2015; Fukuhara et al, 2006; Siqueira et al, 2015; Székelyhidi et al, 2005; Gammons et al, 2013), and, among them, SPHINX31 was recently derived from SPHINX and reported to have much improved potency (Batson et al, 2017). Although high-throughput screening has been commonly used to generate lead compounds in kinase inhibitor projects, we chose to query existing kinase inhibitor libraries and known FDA-approved drugs for their potential abilities to target SRPK1, an approach that offers advantages in expediting structure-activity relationship (SAR) studies and optimizing pharmacological properties.…”
Section: Resultsmentioning
confidence: 99%
“…SR protein kinase 1 has been shown to move into the nucleus in a cell cycle regulated manner [24,45,46] not only at the G2/M phase, but also under other signals such as osmotic changes [47] or growth factor signalling [48,49], as proposed to account for the implication of SRPK1 in tumor development. Many studies find that SRPK1 levels are mostly elevated in different types of tumors [49][50][51] and correlate with cancer progression and worse patient outcome [52,53], highlighting SRPK1 as a target for anticancer treatment [54][55][56][57]. Upon entrance into the nucleus, SRPK1 is found not only in nuclear speckles, which are accepted to be storage sites for splicing factors, but also in the nucleoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Both SRPKs and CLKs are often over-expressed in various cancers emphasizing the relationship between SR protein phosphorylation and splicing as well as the potential for therapeutic intervention through kinase inhibition strategies 27,28 . Indeed, inhibition of SRPKs using the small molecule SRPIN340 induces apoptosis in leukemia cell lines and reduces the splicing of a pro-angiogenic form of VEGF 2931 .…”
Section: Introductionmentioning
confidence: 99%